2012
DOI: 10.1016/j.ijgo.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obstetric vesicovaginal fistula at University Teaching Hospital, Yaoundé, Cameroon

Abstract: status did not put the patient at an increased risk of developing eclampsia. However, some authors have documented an increased risk of developing pregnancy-induced hypertension in employed women because of the stress these patients are under; however, these authors did not evaluate the effect of employment on the risk of convulsion [6]. Prenatal care and bed rest have been recommended as possible preventive measures or a way of delaying the onset of convulsions in pre-eclamptic women who come under this categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The present study shows that the majority (32.4%) of patients were aged 20–29 years at the time of surgical repair. Similar results were reported in Cameroon [11], Burkina Faso [12] and Uganda [13], with 38.4%, 37% and 36.4%, respectively. As in our study, these studies noted that women with fistula stayed longer with this condition before being treated.…”
Section: Discussionsupporting
confidence: 88%
“…The present study shows that the majority (32.4%) of patients were aged 20–29 years at the time of surgical repair. Similar results were reported in Cameroon [11], Burkina Faso [12] and Uganda [13], with 38.4%, 37% and 36.4%, respectively. As in our study, these studies noted that women with fistula stayed longer with this condition before being treated.…”
Section: Discussionsupporting
confidence: 88%
“…This is coherent with the findings of a study done in Cameroon which has shown that knowledge of risk factors influences intent to prevent obstetric fistula recurrence. 35 A similar study in Benin & West Africa revealed that women with obstetric fistula may not know the actual risk factors of obstetric fistula recurrence and how to prevent it. 36 , 37 A descriptive study conducted in Uganda also implies that most of the women with obstetric fistula have inadequate knowledge of whether the condition is repairable and 58.7% do not know whether it is preventable.…”
Section: Discussionmentioning
confidence: 99%
“…A Vesico-Vaginal (V-V) fistula is often the consequence of an injury sustained during a delivery that has been aggravated by protracted or obstructed labor. Tissue ischemia caused by compression of the child's head creates a gap between the woman's vaginal tract and her urinary tract [1]. These V-V fistulae may vary greatly in terms of location, size, and intricacy.…”
Section: Introductionmentioning
confidence: 99%